Distinct Molecular Basis for Differential Sensitivity of the Serotonin Type 3A Receptor to Ethanol in the Absence and Presence of Agonist - Zhang, Li; Hosoi, Masako; Fukuzawa, Misa; Sun, Hui; Rawlings, Robert R.; Weight, Forrest F. (The Journal of biological chemistry, 2002)
Ethanol can potentiate serotonin type 3 (5-HT 3 ) receptor-mediated responses in various neurons and in cells expressing 5-HT 3A receptors. However, the molecular basis for alcohol modulation of 5-HT 3 receptor function has not been determined. Here we report that point mutations of the arginine at amino acid 222 in the N-terminal domain of the 5-HT 3A receptor can alter the EC 50 value of the 5-HT concentration-response curve. Some point mutations at amino acid 222 resulted in spontaneous opening of the 5-HT 3A receptor channel and an inward current activated by ethanol in the absence of agonist. Among these mutant receptors, the amplitude of the current activated by ethanol in the absence of agonist was correlated with the amplitude of the current resulting from spontaneous channel openings, suggesting that the sensitivity of the receptor to ethanol in the absence of agonist is, at least in part, dependent on the preexisting conformational equilibrium of the receptor protein. On the other hand, point mutations that conferred greater sensitivity to ethanol potentiation of agonist-activated responses were less sensitive or insensitive to ethanol in the absence of agonist. For these receptors, the magnitude of the potentiation of agonist-activated responses by ethanol was inversely correlated with the EC 50 values of the 5-HT concentration-response curves, suggesting that these mutations may modulate ethanol sensitivity of the receptor by altering the EC 50 value of the receptor. Thus, distinct molecular processes may determine the sensitivity of 5-HT 3A receptors to ethanol in the absence and presence of agonist.